Exploring the Genetic Regulation of Asexual Sporulation in Zymoseptoria tritici - Tiley, Anna M. M.; Foster, Gary D.; Bailey, Andy M. (Frontiers in Microbiology, 2018)
Zymoseptoria tritici is the causal agent of septoria tritici blotch, a devastating fungal disease of wheat which can cause up to 40 % yield loss. One of the ways in which Z. tritici spreads in the field is via rain splash-dispersed asexual pycnidiospores, however there is currently limited understanding of the genetic mechanisms governing the development of these propagules. In order to explore whether the existing models for conidiation in ascomycete fungi apply to Z. tritici, homologs to the well-characterised Aspergillus nidulans genes abacus (abaA), bristle (brlA), fluffy B (flbB), fluffy C (flbC) and stunted (stuA) were identified and knocked-out by Agrobacterium-mediated transformation. Although deletion of the ZtAbaA, ZtBrlA1 and ZtFlbB genes had no apparent effect on Z. tritici asexual sporulation or on pathogenicity, deletion of ZtFlbC or ZtBrlA2 resulted in mutants with reduced pycnidiospore production compared to the parental IPO323 strain. Deletion of ZtStuA gave non-pigmented mutants with altered vegetative growth and eliminated asexual sporulation and pathogenicity. These findings suggest that the well-established A. nidulans model of asexual sporulation is only partially applicable to Z. tritici, and that this pathogen likely uses additional, as yet uncharacterised genes to control asexual sporulation.